Relationship Between History Of Health Education About Stunting And Knowledge Of Pregnant Women - Wahyu Dewi Hapsari; Sri Martini (Jurnal Profesi Bidan Indonesia, 2023)
Background: Stunting is a global problem, especially in lower middle-class countries with low nutritional status. It is known that data on stunting cases at the Godong 1 Health Center were found to increase from 443 cases in 2020 to 555 in 2021. Purpose: To determine the relationship between the history of health education about stunting and the knowledge of pregnant women at the Godong Halth Center 1. Method: This type of research is quantitative with a cross-sectional design. The population of this study was 85 pregnant women registered at the Godong Health Center 1 in November – December 2021, with a sample of 70 people taken using purposive sampling technique. The data collection tool in this study used a questionnaire which was then analyzed univariately and bivariately. Results: Of the 70 pregnant women, it was found that 55 (79%) had a history of having received health education, and 31 (78%) had sufficient knowledge, while the results of the analysis showed a relationship between health education about stunting and the level of knowledge of pregnant women at the Godong 1 Community Health Center (pvalue 0.000). Conclusion: There is a relationship between the history of health education about stunting and the knowledge of pregnant women